A hazardous boundary of Poly(L-lactic acid) braided stent design: Limited elastic deformability of polymer materials. (February 2023) - Li, Junjie; Cheng, Jie; Hu, Xue; Liu, Jiaming; Tian, Yuan; Wu, Gensheng; Chen, Li; Zhang, Yi; Zhao, Gutian; Ni, Zhonghua
Abstract: Poly (L-lactic acid) (PLLA) braided stents, which are expected to replace metal stents, are promising in peripheral vascular therapy due to their superior biocompatibility. Although various design ideas have been proposed and investigated on metal stents, few researches are related to the design theory of PLLA braided stent. In this article, mechanical performance of PLLA braided stents with different parameters was systematically evaluated, and a design theory based on material properties was proposed. Different from metal materials, the risk of filament deformation beyond elastic zone should be evaluated and controlled in PLLA stent design. The findings were obtained through combination study of experiments and simulations. Design parameters, including pitch angle and stent diameter, played a crucial role in mechanical performance of PLLA braided stent. The deformation of PLLA stents with larger pitch angles and stent diameters was in elastic zone and thus presented better mechanical performance with satisfactory resilience. This work could provide meaningful suggestions for preparing bioresorbable braided stents with suitable design parameters. Graphical abstract: Image 1